Fungi associated with dead branches of Magnolia grandiflora: A case study from Qujing, China - Wijayawardene, Nalin N.; Dai, Dong-Qin; Zhu, Mei-Ling; Wanasinghe, Dhanushka N.; Kumla, Jaturong; Zhang, Gui-Qing; Zhang, Ting-Ting; Han, Li-Su; Tibpromma, Saowaluck; Chen, Huan-Huan (Frontiers in Microbiology, 2022)
As a result of an ongoing survey of micro fungi associated with garden and ornamental plants in Qijing, Yunnan, China, several saprobic fungal taxa were isolated from Magnolia grandiflora. Both morphological and combined SSU, LSU, ITS, tef1 and rpb2 loci phylogenetic analyses (Maximum-Likelihood and Bayesian analyses) were carried out to identify the fungal taxa. Three new species are introduced in Pleosporales; viz., Lonicericola qujingensis (Parabambusicolaceae), Phragmocamarosporium magnoliae and P. qujingensis (Lentitheciaceae). Botryosphaeria dothidea, Diplodia mutila and D. seriata (in Botry-osphaeriaceae) are reported from M. grandiflora for the first time in China. Angustimassarina populi (Amorosiaceae) is reported for the first time on M. grandiflora from China and this is the first report of a member of this genus outside Europe. Shearia formosa is reported for the first time on M. grandiflora from China.